Interaction of estrogen receptor β5 and interleukin 6 receptor in the progression of non–small cell lung cancer. Issue 2 (14th September 2018) - Tang, Hexiao; Bai, Yuquan; Xiong, Lecai; Zhang, Li; Wei, Yanhong; Zhu, Minglin; Wu, Xiaoling; Long, Ding; Yang, Junhui; Yu, Li; Xu, Shufang; Zhao, Jinping
Abstract: Numerous studies have shown that the estrogen receptor beta (ERβ) and interleukin 6 receptor (IL‐6R) had interaction in many tumors, including lung cancer. Previous studies found that ERβ5 exhibits a different biological function compared with the other subtypes of ERβ. Therefore, this study mainly explores the interaction between ERβ5 and IL‐6R in the progression of lung cancer. We found that the expression of ERβ5, IL‐6 and glycoprotein 130 (GP130) were significantly increased ( P  < 0.001) and the 5‐year survival rate with the co‐expression of ERβ5 and GP130 is significantly lower ( P  = 0.0315) in non‐small cell lung cancer (NSCLC) patients. The cell proliferation, invasion, and cell cycle were markedly increased, and the cell apoptotic was markedly inhibited with the concurrent action of ERβ5 and IL‐6 in A549 cells ( P  < 0.05). In addition, the expression of ERβ5, GP130, p‐AKT, and p‐44/42 MAPK was also significantly increased in A549 cells ( P  < 0.05). These results indicate that ERβ5 and GP130 can synergistically promote the progression of NSCLC and maybe combined as an independent prognostic factor in patients. In addition, these results also provide a theoretical basis for the combined targeting therapy of ERβ5 and GP130 in NSCLC. Abstract : We found that the co‐overexpression of ERβ5 and GP130 have a poor prognosis in non‐small cell lung cancer (NSCLC) patients, and it canpromote the biological behavior of lung cancer cells and the expression of key signaling molecules. On this basis, studying the synergy between theERβ5 and GP130 signaling in depth will provide more possibilities for the combined targeting therapy and immunotherapy to lung cancer.